(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Electric vehicles ( EVs) are an alternate means of transport for future as they have great potential to minimize the use of petrol based and other transport fuels that emit high CO2. The components of the BEV framework were discussed here, and a battery electric vehicle (BEV) model was simulated on MATLAB-Simulink. Also, the related components of the electrical system and its corresponding verification equations have been established. In addition, all simulation outcomes were considered. This research provides a basis for further research.